285 Phase I clinical trial evaluating the safety of ADP-A2M10 in patients with MAGE-A10+ head and neck, melanoma, or urothelial tumors. (9th November 2020) - Hong, David; Butler, Marcus; Pachynski, Russell; Sullivan, Ryan; Kebriaei, Partow; Boross-Harmer, Sarah; Frigault, Matthew; Dumbrava, Ecaterina; Sauer, Amy; Brophy, Francine; Navenot, Jean-Marc; Fayngerts, Svetlana; et al.
Abstract : Background: ADP-A2M10 SPEAR T-cells are genetically engineered autologous T-cells that express a high affinity MAGE-A10-specific T-cell receptor targeting MAGE-A10 + tumors in the context of HLA A*02. This trial is no longer enrolling (NCT02989064 ). Methods: This ADP-A2M10 dose escalation trial utilized a modified 3+3 design to evaluate safety and antitumor activity. Patients (pts) with advanced head and neck squamous cell carcinoma (HNSCC), melanoma, or urothelial cancer (UC) were enrolled. Pts were HLA A*02 + with tumors expressing MAGE A10. Pts underwent apheresis; T cells were isolated, transduced with a lentiviral vector containing the MAGE-A10 TCR, and expanded. Eligible pts underwent lymphodepletion with fludarabine and cyclophosphamide prior to receiving ADP-A2M10. ADP-A2M10 was administered at Dose Level (DL) 1 = 0.1 × 10 9, DL2 = >1.2 - 6×10 9, and Expansion = 1.2–15×10 9 transduced cells. Results: As of January 10, 2020, 10 pts (8 male and 2 female) with HNSCC (4), melanoma (3), and UC (3) cancers were treated. Three pts each were treated at DL1 and DL2 and 4 pts were treated in Expansion. The most frequently reported adverse events ≥ Grade 3 were lymphopenia (10 pts), neutropenia (10), anemia (8), leukopenia (7), and thrombocytopenia (5). Two pts reported CRS (1 Grade 1, 1 Grade 3) with resolution. Responses included: 3 pts - stable disease, 5 pts – progressive disease, 1 pt – not evaluable, and 1 pt too early to determine. ADP-A2M10 SPEAR T-cells were detectable in peripheral blood from pts at each dose level and in tumor tissues from several pts at Expansion. Conclusions: There was no evidence of on- or off-target toxicity. Given the minimal antitumor activity and the discovery that MAGE-A10 expression frequently overlaps with MAGE-A4 expression, the clinical program has closed. Several trials with SPEAR T-cells targeting MAGE-A4 are ongoing (https://bit.ly/35htsZK). Trial Registration: NCT02989064 Ethics Approval: The trial was conducted in accordance with the principles of the Declaration of Helsinki and the International Conference on Harmonization Good Clinical Practice guidelines and was approved by local authorities. An independent ethics committee or institutional review board approved the clinical protocol at each participating center. All the patients provided written informed consent before study entry.